Environmental preferences of green sea turtles (Chelonia mydas) for egg-laying on a fringing reef pocket beach, Mayotte Island - Morisseau, Sophie; Jeanson, Matthieu; Charroux, Sarah; Mercky, Yann; Le Bozec, Charles; Charpentier, Michel; Le Gall, Lucas; Delvenne, Cyrielle; Girondot, Marc; Sucré, Elliott; Chevallier, Damien (Frontiers in Marine Science, 2025)
Understanding the spatial ecology of sea turtles is essential to ensure their long-term conservation by the preservation of their environment. The distribution and environmental preferences for egg-laying by the green turtle (Chelonia mydas) were studied on Grande Saziley beach in Mayotte (north of the Mozambique Channel). Green turtle nesting activity was geolocated during night patrols and the depth of specific nests was measured during two field campaigns in 2021 and 2022. Various original environmental parameters related to vegetation and beach morphology were extracted in a GIS environment based on this geolocated data using orthophotography and digital elevation models (DEMs) created by drones prior to field deployments. Sediment samples were also collected from the beach. Thanks to the combination of fieldwork and GIS analysis, this study makes it possible to examine a set of variables, which until now have rarely been studied simultaneously. The results showed that the Grande Saziley beach is a heterogeneous site with the distribution of egg-laying being concentrated in two hotspots. After principal component and GLMM statistical analysis, it appeared that gravid females preferentially lay in a low proportion of coarse sand at the bottom of the nest, at higher elevation and predominantly in surface sand with a low calcium carbonate content. This preference seems to be linked more to elevation, where black sand is mainly found at the top of the beach, rather than an intentional choice based on sand composition. No significant egg-laying site-related variables were found to explain the variations in nest depth. Our study was based on a new approach combining GIS techniques and drone surveys, enabling the collection of environmental parameters, a methodology that can easily be reproduced on other nesting beaches, reducing field workload. However, this work should be continued to assess the viability of sites for clutch survival while considering the spatial and temporal heterogeneity of the environment.